Efficacy and safety of mascara dyeing as an adjunct to Alexandrite and Nd:YAG laser applications for removing thin and white-colored facial and axillary hair - Üstüner, Pelin; Balevi, Ali; Özdemir, Mustafa (Taylor & Francis Inc, 2016)
Introduction: There is no satisfactory and efficient method for long-term removal of white-colored and thin hair. Methods: We conducted a randomised clinical trial of hirsute patients with excessive white and/or thin hair on the face and/or axilla. In Group I (n: 16), the facial hair on one side of the face was painted with a black eyelash mascara immediately before Nd:YAG laser and the other half was only treated by Nd:YAG. In Group II (n: 20), the axillary hair on one side was painted with the mascara before the Alexandrite laser with the other side being only treated by Alexandrite. Results: The terminal hair counts on the painted facial and axillary sides were significantly lower than those on the control sides throughout the study except for the first month. The decrease in the terminal hair count was significant from the beginning of treatment to the second and sixth months on the painted and control facial sides and to the first and sixth months on the axillary sides. Conclusion: Hair coloring with black eyelash mascara is a simple, efficient and safe adjunct to Alexandrite and Nd:YAG laser applications to enhance their clinical efficacy in eliminating white and thin facial or axillary hair.
WOS: 000391344600010
PubMed ID: 27762642
Keywords: Alexandrite laser; Dye; Hair Removal; Lasers; Nd:YAG Laser